Contribution of Individual Polyphenols to Antioxidant Activity of Cotoneaster bullatus and Cotoneaster zabelii Leaves-Structural Relationships, Synergy Effects and Application for Quality Control - Agnieszka Kicel; Aleksandra Owczarek; Paulina Kapusta; Joanna Kolodziejczyk-Czepas; Monika A. Olszewska (MDPI AG, 2020)
Cotoneaster plants are sources of traditional medicines and dietary products, with health benefits resulting from their phenolic contents and antioxidant activity. In this work, active markers of the leaves of C. bullatus and C. zabelii were characterized and evaluated in an integrated phytochemical and biological activity study. Based on UHPLC-PDA-ESI-MS3 analysis, twelve analytes were preselected from the constituents of the hydromethanolic leaf extracts, and two of them—caffeoylmalic acid and quercetin 3--O-β-d-(2″--O-β-d-xylopyranosyl)galactopyranoside (QPH)—were isolated for full identification (NMR spectroscopy: 1H, 13C, COSY, HMBC, HMQC). All selected phenolics contributed to the antioxidant activity of the extracts, which was demonstrated in chemical in vitro tests (DPPH, FRAP, and TBARS) and in a biological model of human plasma exposed to oxidative/nitrative stress induced by peroxynitrite. This contribution was partly due to the synergy between individual polyphenols, evidenced by an isobolographic analysis of the interactions of (−)-epicatechin, chlorogenic acid, and QPH as representatives of three classes of Cotoneaster polyphenols. All twelve markers, including also neochlorogenic acid, cryptochlorogenic acid, procyanidin B2, procyanidin C1, rutin, hyperoside, isoquercitrin, and quercitrin, were thus applied as calibration standards, and a fast, accurate, reproducible, and fully validated RP-HPLC-PDA method for quality control and standardization of the target extracts was proposed.